Characterization and utilization of trichoderma sp. for efficient management of oil palm empty fruit bunch waste in plantations - N. Nurmiati; P. Periadnadi; K. Kartiwan; T.W. Edelwis (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Trichoderma species (Trichoderma sp.) is commonly found in nature, particularly in soil and roots, often thriving in plants rich in cellulose such as oil palm. Therefore, this study aimed to characterize Trichoderma sp. in each substrate as well as to assess cellulolytic and ligninolytic potential in vitro using a specific medium. Characterization and utilization of the plant were examined to efficiently manage empty fruit bunch (EFB) waste in Indonesian oil palm plantations. By exploring the biological, ecological, and biochemical attributes of Trichoderma sp., this study examined the mechanisms associated with efficacy in bioconversion processes and waste remediation.METHODS: A survey method was used to determine sampling locations, and purposive sampling was utilized in the field. Furthermore, several stages were undertaken including isolation, identification, as well as testing of morphology and potential in vitro.RESULTS: The results showed that the growth characteristics of Trichoderma sp. in filling a petri dish spanned approximately five days, forming colonies with a dark green hue. Microscopically, the isolates consisted of conidiophores, phialides, and conidia. Meanwhile, in vitro potential was assessed through cellulolytic and lignocellulolytic assays, with each isolate demonstrating varying capabilities in breaking down cellulose and lignocellulose. The highest cellulase activity (3.55 units per gram) was observed in enzyme starter granules treated with air drying. The highest viability per gram was found in spore inoculum (17.0 x 107) with air drying treatment. The greatest reduction in weight of oil palm EFB waste (65.3 percent) was achieved through the application of Trichoderma sp. enzyme starter granules with air drying treatment. Furthermore, eight isolates demonstrated cellulolytic and ligninolytic potential. Isolates sourced from soil had rapid growth on starter and baglog mediums, indicating potential for subsequent field applications as a biodegradation agent for organic waste.CONCLUSION: Based on the macroscopic (shape and color of mycelium) and microscopic characteristics (mycelium form), a total of eight Trichoderma sp. isolates were obtained. During the potential test, it was observed each isolate had different cellulolytic and ligninolytic activities. This study provided valuable insights into the diversity and enzymatic potential of Trichoderma sp. fungi, underscoring the importance of selecting suitable strains and optimizing cultivation conditions for various biotechnological applications. By exploring cellulolytic and ligninolytic capabilities, the results contributed to the development of more efficient and sustainable strategies for organic waste management and bioconversion. In general, this study represented a significant milestone in the quest for sustainable waste management solutions in agriculture, offering a promising pathway towards mitigating environmental impact and promoting the long-term sustainability of oil palm cultivation.